Mutation Spectrum in RAB3GAP1, RAB3GAP2, and RAB18 and Genotype–Phenotype Correlations in Warburg Micro Syndrome and Martsolf Syndrome. Issue 5 (11th April 2013) - Handley, Mark T.; Morris‐Rosendahl, Deborah J.; Brown, Stephen; Macdonald, Fiona; Hardy, Carol; Bem, Danai; Carpanini, Sarah M.; Borck, Guntram; Martorell, Loreto; Izzi, Claudia; Faravelli, Francesca; Accorsi, Patrizia; et al.
<x xml:space="preserve">Abstract</x> Warburg Micro syndrome (OMIM 60018) and Martsolf syndrome (OMIM 21270) are related autosomal recessive neurodevelopmental disorders. Micro syndrome is more severe and characterized by ocular (microphthalmos, microcornea, congenital cataracts and optic atrophy) and neurodevelopmental pathology (microcephaly, polymicrogyria, hypogenesis of the corpus callosum, severe learning disability and progressive limb spasticity) and hypothalamic hypogonadism. Causative germline mutations have been identified in RAB3GAP1 (41% of families), RAB3GAP2 (7% of families) and RAB18 (5% of families) and result in a strikingly consistent phenotype. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>